2021
DOI: 10.3233/faia210374
|View full text |Cite
|
Sign up to set email alerts
|

Debugging Classical Ontologies Using Defeasible Reasoning Tools

Abstract: A successful application of ontologies relies on representing as much accurate and relevant domain knowledge as possible, while maintaining logical consistency. As the successful implementation of a real-world ontology is likely to contain many concepts and intricate relationships between the concepts, it is necessary to follow a methodology for debugging and refining the ontology. Many ontology debugging approaches have been developed to help the knowledge engineer pinpoint the cause of logical inconsistencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The size of the search space is linked to the size of the ontology; the method would not execute in a reasonable time for a large ontology. Other explanation methods for ontologies only run the logical reasoner a few times ( [1,7]), whereas the CEO method calls it for every explored counterfactual. Hence, it is not yet adequate for debugging large ontologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the search space is linked to the size of the ontology; the method would not execute in a reasonable time for a large ontology. Other explanation methods for ontologies only run the logical reasoner a few times ( [1,7]), whereas the CEO method calls it for every explored counterfactual. Hence, it is not yet adequate for debugging large ontologies.…”
Section: Discussionmentioning
confidence: 99%
“…Its goal is to ask the user for additional knowledge that can reduce the length of proofs and justifications. However, Coetzer and Britz [7] have shown that the debugging approach of OntoDebug can lead to unintuitive results. Despite all the efforts in the development of debugging tools, ontology authors still struggle to debug and repair their ontologies [31].…”
Section: Explaining Owl Ontologiesmentioning
confidence: 99%